DEVELOPMENT OF COMPOSITIONS AND RESEARCH OF METHODS FOR INCREASING THE STRENGTH PROPERTIES OF ORGANOMINERAL THERMOPLASTICS - Ziyamukhamedov , Javohirbek; Tadjikhodjaev , Zakirkhodja (Innovatsion texnologiyalar, 2023)
In this article presented the results of a study on improving the mechanical properties of composite materials based on polyethylene. A composition materials filled with a thermoplastic polymer - polyethylene modified with a kaolin-graphite filler is proposed, which will allow obtaining high-quality products based on local raw materials, simplifying the material composition, and expanding their performance due to improved strength and tribotechnical properties. On the basis of the studies carried out, pipes for the branch parts of oil collection tanks were obtained, which were tested under production conditions.